Effect of Ownership Structures on Financial Performance of Listed Firms in Nairobi Securities Exchange in Kenya - Ng’ang’a, Peter Ndungu; Namusonge, Prof. G. S.; Sakwa, Prof. M.M. (IJRDO - Journal of Business Management, 2016)
The purpose of this study is to determine the effects of ownership structure on firm’s financial performance and will be guided by the following specific objectives: to determine the effects of state ownership on firm’s financial performance; establish the effects of local ownership on firm’s financial performance. Thirdly the study will endeavour to investigate whether foreign ownership affects firm’s financial performance. Finally the study will determined whether ownership structure and managerial shareholding affects firm’s financial performance. The study will adopt Co relational and cross-sectional research designs. The study will use both statistics (quantitative) and themes (qualitative) to develop strong evidence in support of the study variables. The target populations of the study will be the 61 companies listed in Nairobi Securities’ Exchange.